(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article of the author talks about the methodological foundations of modern futurology, in addition, it is said that the focus of futurology on applied research leads to the loss of its philosophical (historical-philosophical) foundations. The connection between the historical sciences and futurology is necessary because reconstruction in history is the same as forecasting in futurology. It should be emphasized here that the gradation of methodology within the framework Известия НАН КР, 2023, №5 171 of scientific knowledge into philosophical, scientific, concrete scientific and experimental is conditional, and it is impossible to create a biased deep scientific concept, bypassing its philosophical foundations. Therefore, it is not very appropriate to expand on the opposite sides of forecasting and theoretical futurology.